О фразеологии скорининских изданий - Томашевич, Т. И. (Kalbotyra, 1986)
The study of the idiomatic phraseology of Skorina’s editions is of great interest for etymologists and historians of the language. Skorina’s texts enable us to affix a date to the rise of many phraseologisms, to examine their evolution and relations between the lexical and phraseological levels of the language.